Clinical, neuropsychological, and metabolic characteristics of transient epileptic amnesia syndrome. Issue 5 (1st March 2014) - Mosbah, Amel; Tramoni, Eve; Guedj, Eric; Aubert, Sandrine; Daquin, Géraldine; Ceccaldi, Mathieu; Félician, Olivier; Bartolomei, Fabrice
Summary: Objective: Transient epileptic amnesia (TEA) is a recently individualized syndrome occurring in adult patients that includes epileptic seizures with amnestic features and interictal memory disturbances. Methods: We investigated the clinical, neuropsychological, and 18F‐FDG positron emission tomography (18F‐FDG‐PET) features of 30 consecutive cases of TEA in our center. Results: The mean age of onset of amnestic seizures was 59 years. Pure acute amnesia was the only epileptic manifestation in 17% of cases. Interictal electroencephalography (EEG) abnormalities were present in 57% on awake recording and in most patients in whom sleep EEG was performed (96%). Nine of 30 patients showed anterograde memory deficit and six of 30 exhibited mild executive functioning impairment. On the autobiographical memory interview (AMI), patients showed a significant deficit for the recent period of the episodic subscale. Outcome under treatment was favorable in the majority of cases. A significant improvement was noted on recollection of autobiographical memory. 18F‐FDG‐PET (22 cases) showed positive correlations between left mesial temporal metabolism levels and anterograde and retrograde memory scores. Significance: TEA is an emerging epileptic syndrome that likely remains misidentified and misdiagnosed. Neurometabolic data support a dysfunction of a hippocampal‐neocortical network sustaining episodic memory. A PowerPoint slide summarizing this article is available for download in the Supporting Information section here .